Grain boundary diffusion source coating and method for improving residual magnetism of (Ce, R)-Fe-B magnet

By using La1-x-yAlxCuy as the grain boundary diffusion source on the cerium-containing magnet, the (Ce, R, La)2Fe14B shell is formed, which solves the problem of diffusion of heavy rare earth elements to reduce remanence magnetism and direct addition of La to reduce coercion in the prior art. The problem of force achieves the effect of improving the residual magnetism and coercivity of the cerium-containing magnet, while reducing costs and production difficulty.

CN119274953APending Publication Date: 2025-01-07CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411381480.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art has contradictions in improving the coercive force and residual magnetism of cerium-containing magnets. Diffusion of heavy rare earth elements will reduce the residual magnetism and magnetic energy accumulation, while adding La directly reduces the coercive force, making it difficult to not reduce the coercive force. .

Method used

La1-x-yAlxCuy is used as the grain boundary diffusion source coating material, and La1-x-yAlxCuy alloy is prepared by smelting, hydrogen breaking and crushing and powdering under the protection of anhydrous ethanol are carried out to form La1-x-yAlxCuy powder and coated It is coated on the surface of the cerium-containing magnet, and undergoes grain boundary diffusion and tempering to form (Ce, R, La)2Fe14B shell to optimize the magnet grain boundary structure.

Benefits of technology

The remanent magnetism and coercive force of the cerium-containing magnet is improved, the saturation magnetization of the magnetic main phase is enhanced, the cost is reduced, and the feasibility of batch preparation is realized on the existing production lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274953A_ABST
    Figure CN119274953A_ABST
Patent Text Reader

Abstract

The invention relates to a grain boundary diffusion source coating material and method for improving residual magnetism of a (Ce, R)-Fe-B magnet, belongs to the technical field of rare earth permanent magnet materials, and aims to solve the problem that the coercive force of the magnet cannot be reduced when the La element is applied to the cerium-containing magnet in the conventional method for applying the La element to the cerium-containing magnet. The invention relates to a grain boundary diffusion source coating for improving the residual magnetism of a (Ce, R)-Fe-B magnet, the grain boundary diffusion source coating is powder, comprises elements La, Al and Cu, and is expressed as La1-x-yAlxCuy according to atomic percent, x is more than or equal to 25 and less than or equal to 0.35, and y is more than or equal to 0.05 and less than or equal to 0.15. The La1-x-yAlxCuy grain boundary diffusion source coating provided by the invention can improve the residual magnetism and coercive force of the cerium-containing magnet at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth permanent magnet materials, and in particular to a grain boundary diffusion source coating for improving the remanence of a (Ce, R)-Fe-B magnet and a method thereof. Background Art

[0002] Rare earth permanent magnet materials are widely used in electromechanical, information, robotics and intelligent manufacturing. In recent years, with the rapid development of new energy vehicles, wind power generation and energy-efficient home appliances, the demand for rare earth permanent magnet materials has increased day by day. As the main raw materials, PrNd rare earths are overused and consumed in large quantities. Since rare earth elements are mostly enriched in the earth's crust in a co-existing manner, when rare earth separation companies extract Nd and Pr, high-abundance rare earth Ce and other resources have been accumulated for a long time, which restricts the balanced utilization and long-term development of my country's rare earth resources.

[0003] With the successful large-scale production of high-abundance cerium magnets, using Ce to replace Nd to prepare high-abundance rare earth permanent magnets can not only significantly reduce the raw material cost of rare earth permanent magnets, but also has extremely important strategic significance for achieving efficient and balanced utilization of rare earth resources. 14 The intrinsic magnetic properties of compound B (including saturation magnetization 4πMs, room temperature magnetocrystalline anisotropy field HA, Curie temperature Tc) are significantly lower than those of Nd2Fe 14 B. Adding Ce to NdFeB magnets will significantly reduce the magnetic properties of the magnets.

[0004] At present, the overall magnetic properties of existing cerium-containing magnets are relatively low, which greatly limits the application field of cerium-containing magnets. The grain boundary diffusion of heavy rare earth elements can improve the coercivity of cerium-containing magnets to a certain extent, but heavy rare earth elements are expensive, and the grain boundary diffusion of heavy rare earth elements will reduce the remanence and magnetic energy product of cerium-containing magnets. Existing studies have found that when La with a larger radius is added to the 2:14:1 compound containing Ce, it can not only make the valence state of Ce more inclined to +3, but also make the 2:14:1 phase continue to be maintained, which plays a vital role in improving the performance of magnets; however, directly adding La to the cerium-containing permanent magnet alloy makes it easier to form α-Fe phase in the cerium-containing permanent magnet, which will reduce the coercivity of the magnet. Therefore, how to improve the remanence of cerium-containing magnets without reducing the coercivity has always been a widely pursued goal in the industry. Summary of the invention

[0005] In view of the above analysis, the embodiments of the present invention aim to provide a grain boundary diffusion source coating and method for improving the remanence of (Ce, R)-Fe-B magnets, so as to solve at least one of the following problems: 1. The existing method of applying the La element to cerium-containing magnets will reduce the coercive force of the magnets; 2. The existing method of applying the La element to cerium-containing magnets cannot guarantee that when the La element is applied to the cerium-containing magnets, the magnets have good coercive force and remanence at the same time.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions:

[0007] The present invention provides a grain boundary diffusion source coating for improving the remanence of a (Ce, R)-Fe-B magnet. The grain boundary diffusion source coating is a powder, comprising elements La, Al and Cu, expressed as La in atomic percentage. 1-x-y Al x Cu y , where 25≤x≤0.35, 0.05≤y≤0.15.

[0008] Furthermore, the average grain size SMD of the grain boundary diffusion source coating is 1 to 2 μm.

[0009] The present invention also provides a method for improving the remanence of a (Ce, R)-Fe-B magnet, using the grain boundary diffusion source coating according to claim 1 or 2, comprising the following steps:

[0010] S1: Cut the original cerium-containing magnet that meets the mass percentage requirements into a cylindrical shape, clean the oil stains on the surface of the magnet, and polish with sandpaper to remove the oxide layer on the surface of the magnet;

[0011] S2: According to the alloy mass percentage chemical formula La 1-x-y Al x Cu y Configure the raw materials, where 0.25≤x≤0.35, 0.05≤y≤0.15;

[0012] S3: Preparation of La by smelting 1-x-y Al x Cu y Diffusion source alloy;

[0013] S4: La 1-x-y Al x Cu y The diffusion source alloy is roughly crushed to obtain La 1-x-y Al x Cu y Diffusion source alloy coarse powder;

[0014] S5: La 1-x-y Al x Cu yDiffusion source alloy coarse powder is hydrogen-crushed to obtain La 1-x-y Al x Cu y Diffusion source alloy hydrogen powder breaking;

[0015] S6: La 1-x-y Al x Cu y The diffusion source alloy is crushed and powdered under the protection of anhydrous ethanol to obtain La 1-x-y Al x Cu y Diffusion source alloy powder slurry;

[0016] S7: La 1-x-y Al x Cu y The diffusion source alloy powder slurry is applied to the surface of the cylindrical magnet in step S1 to obtain an attached diffusion source magnet;

[0017] S8: subjecting the attached diffusion source magnet to grain boundary diffusion treatment and then to tempering treatment to obtain (Ce, R, La)2Fe 14 Grain boundary diffusion of cerium-containing magnets in the B shell.

[0018] Furthermore, in step S3, the smelting is one of electric arc furnace smelting, induction smelting, rapid quenching or rapid solidification.

[0019] Furthermore, in step S5, the hydrogen-crushing powder making process is: La obtained in step S4 is 1-x-y Al x Cu y The diffusion source alloy coarse powder is subjected to hydrogen cracking treatment, and is crushed by hydrogen absorption at room temperature and 0.1 MPa pressure to obtain hydrogen-crushed powder of 20 to 150 μm, without dehydrogenation treatment.

[0020] Further, in step S6, the La 1-x-y Al x Cu y In the diffusion source alloy powder slurry, anhydrous ethanol and La 1-x- y Al x Cu y The mass ratio of the diffusion source alloy powder is 1:1.

[0021] Furthermore, in step S7, the weight increase of the magnet with attached diffusion source is 0.4-0.6% of the weight of the original magnet.

[0022] Furthermore, in step S8, the grain boundary diffusion treatment temperature is 850-950° C., and the grain boundary diffusion treatment time is 3-24 hours.

[0023] Furthermore, in step S8, the tempering treatment temperature is 400° C. to 700° C., and the tempering treatment time is 2 to 5 hours.

[0024] The present invention also provides a (Ce, R)-Fe-B magnet, wherein the outer layer of the main phase grain of the (Ce, R)-Fe-B magnet comprises (Ce, R, La)2Fe 14 B shell.

[0025] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0026] 1. Due to Ce2Fe 14 The saturation magnetization of B compound is significantly lower than that of Nd2Fe 14 B. Adding Ce to NdFeB magnets will significantly reduce the remanence of the magnets. The existing technology uses heavy rare earth element grain boundary diffusion to increase the coercivity of cerium-containing magnets, but it will reduce the remanence and magnetic energy product of cerium magnets. At the same time, due to La2Fe 14 B has poor phase formation ability. Directly adding La to the permanent magnet alloy will reduce the coercive force of the magnet, and single La is easily oxidized. 1-x- y Al x Cu y , so that La element enters the main phase grains of the magnet, forming a shell structure (Ce, R, La)2Fe on the outer layer of the main phase grains 14 B, while optimizing the magnet grain boundary structure; the saturation magnetization intensity of this main phase shell is higher than that of (Ce, R)2Fe 14 B. The saturation magnetization intensity of the magnetic main phase is greatly increased, which can simultaneously improve the remanence and coercive force of the cerium-containing magnet.

[0027] 2. The present invention uses La 1-x-y Al x Cu y The alloy powder is used as a diffusion source coating, wherein 0.25≤x≤0.35, 0.05≤y≤0.15, and the average particle size SMD of the coating powder is 1-2 μm. The diffusion source has good oxidation resistance and low cost, and the grain boundary diffusion time is short.

[0028] 3. Grain boundary diffusion source coating La of the present invention 1-x-y Al x Cu y The alloy powder can be coated onto the surface of the (Ce, R)-Fe-B magnet substrate by immersion, spraying or screen printing, etc. It has wide applicability and can be quickly prepared and produced in batches on existing production lines.

[0029] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0031] Figure 1 The (Ce, R, La)2Fe 14 Microstructure of grain boundary diffused Ce-containing magnet in B shell. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0033] The present invention provides a grain boundary diffusion source coating for improving the remanence of a (Ce, R)-Fe-B magnet. The grain boundary diffusion source coating is a powder, comprising elements La, Al and Cu, expressed as La in atomic percentage. 1-x-y Al x Cu y , wherein 25≤x≤0.35, 0.05≤y≤0.15; the average particle size SMD of the grain boundary diffusion source coating is 1 to 2 μm.

[0034] The La 1-x-y Al x Cu y The grain boundary diffusion source coating is applicable to all (Ce, R)-Fe-B magnets; preferably, the (Ce, R)-Fe-B original magnet contains Ce, R is at least one of Nd and Pr and does not contain La, and the mass percentage general formula is (Ce x ,R 1-x ) a Fe 余 B 0.9-1.25 TM b , where: 0.1≤x≤0.9, 29.5≤a≤32, 0.5≤b≤3, TM is one or more of Co, Al, Cu, Sn, Ga, Nb, Ti, and Zr.

[0035] The present invention also provides a method for improving the remanence of a (Ce, R)-Fe-B magnet, using the above-mentioned grain boundary diffusion source coating, comprising the following steps:

[0036] S1: Cut the original cerium-containing magnet that meets the mass percentage requirements into a cylindrical shape, clean the oil stains on the surface of the magnet, and polish with sandpaper to remove the oxide layer on the surface of the magnet;

[0037] S2: According to the alloy mass percentage chemical formula La 1-x-y Al x Cu y Configure the raw materials, where 0.25≤x≤0.35, 0.05≤y≤0.15;

[0038] S3: Preparation of La by smelting 1-x-y Al x Cu y Diffusion source alloy;

[0039] S4: La 1-x-y Al x Cu y The diffusion source alloy is roughly crushed to obtain La 1-x-y Al x Cu y Diffusion source alloy coarse powder;

[0040] S5: La 1-x-y Al x Cu y Diffusion source alloy coarse powder is hydrogen-crushed to obtain La 1-x-y Al x Cu y Diffusion source alloy hydrogen powder breaking;

[0041] S6: La 1-x-y Al x Cu y The diffusion source alloy is crushed and powdered under the protection of anhydrous ethanol to obtain La 1-x-y Al x Cu y Diffusion source alloy powder slurry;

[0042] S7: La 1-x-y Al x Cu y The diffusion source alloy powder slurry is applied to the surface of the cylindrical magnet in step S1 to obtain an attached diffusion source magnet;

[0043] S8: The attached diffusion source magnet is subjected to diffusion treatment and then tempered to obtain a (Ce, R, La)2Fe 14 Grain boundary diffusion of cerium-containing magnets in the B shell.

[0044] Specifically, in step S3, La is prepared by smelting 1-x-y Al x Cu y The diffusion source alloy can be smelted by one of arc furnace smelting, induction melting, rapid quenching or rapid solidification; the arc melting, induction melting, rapid quenching and rapid solidification are all conventional melting processes, and their process parameters are all conventional parameters.

[0045] Specifically, in step S5, La 1-x-y Al x Cu y Diffusion source alloy coarse powder is hydrogen-crushed to obtain La 1-x- y Al x Cu y Diffusion source alloy hydrogen powder, hydrogen powder making process is: La obtained in step S4 1-x-y Al x Cu y The diffusion source alloy coarse powder is subjected to hydrogen cracking treatment, and is crushed by hydrogen absorption at room temperature and 0.1 MPa pressure to obtain hydrogen-crushed powder of 20 to 150 μm, without dehydrogenation treatment.

[0046] Specifically, in step S6, La 1-x-y Al x Cu y The diffusion source alloy is crushed and powdered under the protection of anhydrous ethanol to obtain La 1-x-y Al x Cu y Diffusion source alloy powder slurry; the La 1-x-y Al x Cu y The average particle size SMD of the diffusion source alloy powder slurry is 1-2 μm, and the anhydrous ethanol and La in the slurry 1-x-y Al x Cu y The mass ratio of the diffusion source alloy powder is 1:1, and satisfying this mass ratio can ensure the coating performance of the subsequent slurry.

[0047] Specifically, in step S7, La 1-x-y Al x Cu y The diffusion source alloy powder slurry is coated on the surface of the magnet in step S1 to obtain a magnet with an attached diffusion source. It should be noted that the coating amount of the diffusion source will affect the magnetic properties of the magnet after diffusion. Therefore, in order to ensure the performance of the magnet, the coating La 1-x-y Al x Cu yAfter the source alloy powder slurry is diffused, the weight gain of the magnet should be controlled between 0.4 and 0.6% of the original magnet weight. The coating method is one of immersion, spraying or screen printing. If the coating method is immersion, the magnet surface includes the entire surface of the magnet. If the coating method is spraying or screen printing, the magnet surface refers to the upper and lower surfaces of the magnet, excluding the side surfaces.

[0048] Specifically, in step S8, the attached diffusion source magnet is subjected to diffusion treatment and then tempered to obtain a (Ce, R, La)2Fe 14 The B shell of the grain boundary diffusion cerium-containing magnet; wherein the grain boundary diffusion treatment temperature is 850-950°C, the grain boundary diffusion treatment time is 3-24h, preferably, the grain boundary diffusion treatment time is 6-10h; the tempering treatment temperature is 400°C-700°C, and the tempering treatment time is 2-5h. The outer layer of the main phase grains of the final grain boundary diffusion cerium-containing magnet includes (Ce, R, La)2Fe 14 B shell.

[0049] It should be noted that for RE2Fe 14 In compound B, the RE atoms in the crystal lattice occupy the 4f and 4g positions, and the 4f position has a smaller volume; in RE2Fe 14 In the B lattice, the rare earth element RE usually presents a +3 valence. Due to the electronic structure, in Ce2Fe 14 In B, Ce has a variable valence state, Ce can be either +3 or +4. The smaller the radius, the +4 Occupies the 4f crystal site with a smaller crystal volume, and Ce +4 Ce2Fe is not magnetic. 14 The saturation magnetization intensity of B compound is low. 1-x-y Al x Cu y , so that La element enters the main phase grains of the magnet, forming a shell structure (Ce, R, La)2Fe on the outer layer of the main phase grains 14 B, while optimizing the magnet grain boundary structure; La enters the main phase to replace Ce, causing lattice expansion, and the saturation magnetization intensity of this main phase shell is higher than that of (Ce, R)2Fe 14 B, the saturation magnetization of the magnetic main phase increases significantly, thereby increasing the remanence of the cerium-containing magnet. 14 B has poor phase formation ability, and La2Fe 14 The magnetocrystalline anisotropy field H of B A Only 20kOe, so directly adding La into the permanent magnet alloy makes it easier to form α-Fe phase in the magnet and reduce the coercive force of the magnet; 1-x-y Al x Cuy , so that La element enters the main phase grains of the magnet, forming a shell structure (Ce, R, La)2Fe on the outer layer of the main phase grains 14 B, can solve the above problems well and can simultaneously improve the remanence and coercive force of cerium-containing magnets.

[0050] Example 1

[0051] The composition of the original magnet used in this embodiment is (Ce 0.1 Nd 0.9 ) 29.5 Fe bal B 0.9 TM 1.1 (TM=Al, Co, Cu, Ga, Ti, Zr)(wt.%), the remanence of the magnet is 14.2 kGs, the coercive force is 12.19 kOe, and the magnetic energy product is 49.58 MGOe.

[0052] This embodiment provides a grain boundary diffusion source coating for improving the remanence of the original magnet. The grain boundary diffusion source coating is a powder, including the elements La, Al and Cu, expressed as La in atomic percentage. 60 Al 25 Cu 15 ;

[0053] The method of improving the remanence of (Ce, R)-Fe-B magnets in this embodiment is to use the above-mentioned grain boundary diffusion source coating material La 60 Al 25 Cu 15 Completed, including the following steps:

[0054] S1: Cut the original cerium-containing magnet into Φ10*5mm 3 The cylindrical shape of the magnet is cleaned to remove the oil stains on the surface of the magnet, and the oxide layer on the surface of the magnet is removed by sandpaper polishing;

[0055] S2: According to the alloy mass percentage chemical formula La 60 Al 25 Cu 15 Prepare raw materials;

[0056] S3: Preparation of La by non-consumable arc furnace smelting 60 Al 25 Cu 15 For the diffusion source alloy, each sample was melted repeatedly 4 times to ensure the uniformity of the alloy;

[0057] S4: La 60 Al 25 Cu 15 The diffusion source alloy was roughly crushed to obtain La particles with a diameter of about 0.5 cm. 60 Al25 Cu 15 Diffusion source alloy coarse powder;

[0058] S5: La 60 Al 25 Cu 15 Diffusion source alloy coarse powder is hydrogen-crushed to obtain La 60 Al 25 Cu 15 Diffusion source alloy hydrogen powder breaking;

[0059] The process of hydrogen crushing and powder making is as follows: La obtained in step S4 is 60 Al 25 Cu 15 The diffusion source alloy coarse powder is subjected to hydrogen cracking treatment, and is crushed by hydrogen absorption at room temperature and 0.1 MPa pressure to obtain hydrogen-crushed powder of 20 to 150 μm, without dehydrogenation treatment.

[0060] S6: La 60 Al 25 Cu 15 The diffusion source alloy is crushed and powdered under the protection of anhydrous ethanol to obtain La 60 Al 25 Cu 15 Diffusion source alloy powder slurry;

[0061] Among them, the La 60 Al 25 Cu 15 The average particle size SMD of the diffusion source alloy powder slurry is 1-2 μm, and the anhydrous ethanol and La in the slurry 60 Al 25 Cu 15 The mass ratio of the diffusion source alloy powder is 1:1.

[0062] S7: By soaking 60 Al 25 Cu 15 The diffusion source alloy powder slurry is coated on the surface of the cylindrical magnet in step S1 to obtain an attached diffusion source magnet. After coating with the slurry, the weight gain of the magnet is controlled to be 0.5%;

[0063] S8: The attached diffusion source magnet is diffused at 850°C for 10 hours, and then tempered at 660°C for 2 hours to obtain a (Ce, R, La)2Fe 14 Grain boundary diffusion of cerium-containing magnets in the B shell.

[0064] Example 2

[0065] The composition of the original magnet used in this embodiment is (Ce 0.35 Nd 0.7 )30 Fe bal B 1.0 TM 1.1 (TM=Al, Co, Cu, Nb)(wt.%), the remanence of the magnet is 13.16 kGs, the coercive force is 12.25 kOe, and the magnetic energy product is 42.30 MGOe.

[0066] This embodiment provides a grain boundary diffusion source coating for improving the remanence of the original magnet. The grain boundary diffusion source coating is a powder, including the elements La, Al and Cu, expressed as La in atomic percentage. 60 Al 30 Cu 10 ;

[0067] The method of improving the remanence of (Ce, R)-Fe-B magnets in this embodiment is to use the above-mentioned grain boundary diffusion source coating material La 60 Al 30 Cu 10 Completed, including the following steps:

[0068] S1: Cut the original cerium-containing magnet into Φ10*5mm 3 The cylindrical shape of the magnet is cleaned to remove the oil stains on the surface of the magnet, and the oxide layer on the surface of the magnet is removed by sandpaper polishing;

[0069] S2: According to the alloy mass percentage chemical formula La 60 Al 30 Cu 10 Prepare raw materials;

[0070] S3: Preparation of La by non-consumable arc furnace smelting 60 Al 30 Cu 10 For the diffusion source alloy, each sample was melted repeatedly 4 times to ensure the uniformity of the alloy;

[0071] S4: La 60 Al 30 Cu 10 The diffusion source alloy was roughly crushed to obtain La particles with a diameter of about 0.5 cm. 60 Al 30 Cu 10 Diffusion source alloy coarse powder;

[0072] S5: La 60 Al 30 Cu 10 Diffusion source alloy coarse powder is hydrogen-crushed to obtain La 60 Al 30 Cu 10 Diffusion source alloy hydrogen powder breaking;

[0073] The process of hydrogen crushing and powder making is as follows: La obtained in step S4 is 60 Al 30 Cu 10 The diffusion source alloy coarse powder is subjected to hydrogen cracking treatment, and is crushed by hydrogen absorption at room temperature and 0.1 MPa pressure to obtain hydrogen-crushed powder of 20 to 150 μm, without dehydrogenation treatment.

[0074] S6: La 60 Al 30 Cu 10 The diffusion source alloy is crushed and powdered under the protection of anhydrous ethanol to obtain La 60 Al 30 Cu 10 Diffusion source alloy powder slurry;

[0075] Among them, the La 60 Al 30 Cu 10 The average particle size SMD of the diffusion source alloy powder slurry is 1-2 μm, and the anhydrous ethanol and La in the slurry 60 Al 30 Cu 10 The mass ratio of the diffusion source alloy powder is 1:1.

[0076] S7: By soaking 60 Al 30 Cu 10 The diffusion source alloy powder slurry is coated on the surface of the cylindrical magnet in step S1 to obtain an attached diffusion source magnet. After coating with the slurry, the weight gain of the magnet is controlled to be 0.5%;

[0077] S8: The attached diffusion source magnet is diffused at 900°C for 10 hours, and then tempered at 700°C for 2 hours to obtain (Ce, R, La)2Fe 14 Grain boundary diffusion of cerium-containing magnets in the B shell.

[0078] Example 3

[0079] The composition of the original magnet used in this embodiment is (Y 0.05 Ce 0.9 RE 0.05 ) 32 Fe bal B 1.25 TM 1.4 (RE=Pr,Nd;TM=Al,Co,Cu,Sn,Zr)(wt.%), the remanence of the magnet is 10.05kGs, the coercive force is 3.61kOe, and the magnetic energy product is 19.35MGOe.

[0080] This embodiment provides a grain boundary diffusion source coating for improving the remanence of the original magnet. The grain boundary diffusion source coating is a powder, including the elements La, Al and Cu, expressed as La in atomic percentage. 60 Al 35 Cu5;

[0081] The method of improving the remanence of (Ce, R)-Fe-B magnets in this embodiment is to use the above-mentioned grain boundary diffusion source coating material La 60 Al 35 Cu5 is completed, including the following steps:

[0082] S1: Cut the original cerium-containing magnet into Φ10*5mm 3 The cylindrical shape of the magnet is cleaned to remove the oil stains on the surface of the magnet, and the oxide layer on the surface of the magnet is removed by sandpaper polishing;

[0083] S2: According to the alloy mass percentage chemical formula La 60 Al 35 Cu5 configuration raw materials;

[0084] S3: Preparation of La by non-consumable arc furnace smelting 60 Al 35 For Cu5 diffusion source alloy, each sample was repeatedly melted 4 times to ensure the uniformity of the alloy;

[0085] S4: La 60 Al 35 The Cu5 diffusion source alloy was roughly crushed to obtain La 60 Al 35 Cu5 diffusion source alloy coarse powder;

[0086] S5: La 60 Al 35 The Cu5 diffusion source alloy coarse powder was hydrogenated to obtain La 60 Al 35 Cu5 diffusion source alloy hydrogen powder breaking;

[0087] The process of hydrogen crushing and powder making is as follows: La obtained in step S4 is 60 Al 35 The Cu5 diffusion source alloy coarse powder was subjected to hydrogen crushing treatment, and hydrogen was absorbed and crushed at room temperature and 0.1 MPa pressure to obtain hydrogen-crushed powder of 20 to 150 μm, without dehydrogenation treatment.

[0088] S6: La 60 Al 35 The Cu5 diffusion source alloy was crushed and powdered under the protection of anhydrous ethanol to obtain La 60 Al 35 Cu5 diffusion source alloy powder slurry;

[0089] Among them, the La 60 Al 35 The average particle size SMD of Cu5 diffusion source alloy powder slurry is 1-2 μm. 60 Al 35 The mass ratio of the Cu5 diffusion source alloy powder is 1:1.

[0090] S7: By soaking 60 Al 35 Cu5 diffusion source alloy powder slurry is coated on the surface of the cylindrical magnet in step S1 to obtain an attached diffusion source magnet. After coating with the slurry, the weight gain of the magnet is controlled at 0.5%;

[0091] S8: The attached diffusion source magnet is diffused at 950°C for 6 hours, and then tempered at 400°C for 2 hours to obtain a (Ce, R, La)2Fe 14 Grain boundary diffusion of cerium-containing magnets in the B shell.

[0092] Comparative Example 1-1

[0093] The original magnet composition of this comparative example is the same as that of Example 1, except that the grain boundary diffusion source coating used is conventional heavy rare earth Dy, and the remaining steps and process parameters are the same as those of Example 1.

[0094] Comparative Example 1-2

[0095] The original magnet composition of this comparative example is the same as that of Example 1, except that the grain boundary diffusion source coating used is La 50 Cu 50 The remaining steps and process parameters are the same as those in Example 1.

[0096] Comparative Examples 1-3

[0097] The composition of the original magnet used in this comparative example is (Ce 0.1 Nd 0.9 ) 29.5 Fe bal B 0.9 TM 1.1 (TM=Al, Co, Cu, Ga, Ti, Zr)(wt.%), the remanence of the magnet is 14.2 kGs, the coercive force is 12.19 kOe, and the magnetic energy product is 49.58 MGOe.

[0098] This comparative example provides a grain boundary diffusion source coating for improving the remanence of the original magnet. The grain boundary diffusion source coating is a powder, including the elements La, Al and Cu, expressed as La in atomic percentage. 60 Al 25 Cu15 ;

[0099] The method of improving the remanence of (Ce, R)-Fe-B magnets in this embodiment is to use the above-mentioned grain boundary diffusion source coating material La 60 Al 25 Cu 15 Completed, including the following steps:

[0100] S1: Cut the original cerium-containing magnet into Φ10*5mm 3 The cylindrical shape of the magnet is cleaned to remove the oil stains on the surface of the magnet, and the oxide layer on the surface of the magnet is removed by sandpaper polishing;

[0101] S2: According to the alloy mass percentage chemical formula La 60 Al 25 Cu 15 Prepare raw materials;

[0102] S3: Preparation of La by non-consumable arc furnace smelting 60 Al 25 Cu 15 For the diffusion source alloy, each sample was melted repeatedly 4 times to ensure the uniformity of the alloy;

[0103] S4: La 60 Al 25 Cu 15 The diffusion source alloy was roughly crushed to obtain La particles with a diameter of about 0.5 cm. 60 Al 25 Cu 15 Diffusion source alloy coarse powder;

[0104] S5: La 60 Al 25 Cu 15 Diffusion source alloy coarse powder is hydrogen-crushed to obtain La 60 Al 25 Cu 15 Diffusion source alloy hydrogen powder breaking;

[0105] The process of hydrogen crushing and powder making is as follows: La obtained in step S4 is 60 Al 25 Cu 15 The diffusion source alloy coarse powder is subjected to hydrogen cracking treatment, and is crushed by hydrogen absorption at room temperature and 0.1 MPa pressure to obtain hydrogen-crushed powder of 20 to 150 μm, without dehydrogenation treatment.

[0106] S6: La 60 Al 25 Cu 15 The diffusion source alloy is crushed and powdered under the protection of anhydrous ethanol to obtain La 60 Al 25Cu 15 Diffusion source alloy powder slurry;

[0107] Among them, the La 60 Al 25 Cu 15 The average particle size SMD of the diffusion source alloy powder slurry is 1-2 μm, and the anhydrous ethanol and La in the slurry 60 Al 25 Cu 15 The mass ratio of the diffusion source alloy powder is 1:1.

[0108] S7: By soaking 60 Al 25 Cu 15 The diffusion source alloy powder slurry is coated on the surface of the cylindrical magnet in step S1 to obtain an attached diffusion source magnet. After coating with the slurry, the weight gain of the magnet is controlled at 0.7%;

[0109] S8: The attached diffusion source magnet is diffused at 800°C for 10 hours, and then tempered at 750°C for 1 hour to obtain (Ce, R, La)2Fe 14 Grain boundary diffusion of cerium-containing magnets in the B shell.

[0110] Comparative Example 2-1

[0111] The original magnet composition of this comparative example is the same as that of Example 2, except that the grain boundary diffusion source coating used is conventional heavy rare earth Dy, and the remaining steps and process parameters are the same as those of Example 1.

[0112] Comparative Example 2-2

[0113] The original magnet composition of this comparative example is the same as that of Example 2, except that the grain boundary diffusion source coating used is La 80 Al 20 The remaining steps and process parameters are the same as those in Example 2.

[0114] The microstructure of the grain boundary diffusion cerium-containing magnet finally obtained in this comparative example is:

[0115] Comparative Example 3-1

[0116] The original magnet composition of this comparative example is the same as that of Example 3, except that the grain boundary diffusion source coating used is conventional heavy rare earth Dy, and the remaining steps and process parameters are the same as those of Example 1.

[0117] Comparative Example 3-2

[0118] The original magnet composition of this comparative example is the same as that of Example 3, except that the grain boundary diffusion source coating used is La 50 Fe 40 Al10 The remaining steps and process parameters are the same as those in Example 3.

[0119] Comparative Example 3-3

[0120] The original magnet composition of this comparative example is the same as that of Example 3, except that the grain boundary diffusion source coating used is La 44 Al 40 Cu 16 The remaining steps and process parameters are the same as those in Example 3.

[0121] The magnetic properties of the embodiment and comparative example magnets are shown in Table 1

[0122]

[0123]

[0124] Comparative Example 1-1 is to use conventional heavy rare earth Dy for grain boundary diffusion treatment, and the remanence B of the magnet is r Reduce 0.20kGs, magnetic energy product (BH) m Reduce 2.93MGOe; Comparative Example 1-2 uses an atomic percentage of La 50 Cu 50 The alloy is treated with grain boundary diffusion, and the remanence of the magnet is B r Reduce 0.15kGs, magnetic energy product (BH) m Reduce 2.58MGOe; in Comparative Examples 1-3, the grain boundary diffusion source coating La 60 Al 25 Cu 15 During the diffusion process, some process parameters of the diffusion and tempering process do not meet the requirements of the present invention, and the remanence B r Reduce 0.10kGs, magnetic energy product (BH) m Reduce 1.98MGOe; the magnet of Example 1 uses La 60 Al 25 Cu 15 After grain boundary diffusion treatment, the remanent magnetism B r Increase by 0.22kGs, and the coercive force H of the magnet cj Also increased from 12.16kOe to 13.5kOe, magnetic energy product (BH) m Increase 1.14MGOe. Grain boundary diffusion La 60 Al 25 Cu 15 At the same time, the remanence, coercive force and magnetic energy product of the cerium-containing magnet are increased, achieving obvious beneficial effects.

[0125] Comparative Example 2-1 uses conventional heavy rare earth Dy for grain boundary diffusion treatment, and the remanence Br Reduce 0.24kGs, magnetic energy product (BH) m Reduce 2.54MGOe; Comparative Example 2-2 uses an atomic percentage of La 80 Al 20 The alloy is treated with grain boundary diffusion, and the remanence of the magnet is B r Reduce 0.53kGs, magnetic energy product (BH) m Reduce 4.32MGOe; the magnet of Example 2 uses La 60 Al 30 Cu 10 After grain boundary diffusion treatment, the remanent magnetism B r Increase by 0.24kGs, and the coercive force H of the magnet cj Also increased from 12.16kOe to 15.51kOe, magnetic energy product (BH) m Increase 1.65MGOe. Grain boundary diffusion La 60 Al 30 Cu 10 At the same time, the remanence, coercive force and magnetic energy product of the cerium-containing magnet are increased, achieving obvious beneficial effects.

[0126] Comparative Example 3-1 uses conventional heavy rare earth Dy for grain boundary diffusion treatment, and the remanence B of the magnet is r Reduce 0.26kGs, magnetic energy product (BH) m Reduce 0.36MGOe; Comparative Example 3-2 uses an atomic percentage of La 50 Fe 40 Al 10 The alloy is treated with grain boundary diffusion, and the remanence of the magnet is B r Reduce 0.22kGs, magnetic energy product (BH) m Reduce 3.25MGOe; Comparative Example 3-3 uses an atomic percentage of La 44 Al 40 Cu 16 The alloy was treated with grain boundary diffusion, and the remanence Br of the magnet was reduced by 0.19 kGs, and the magnetic energy product (BH)m was reduced by 2.45 MGOe. 60 Al 30 Cu 10 After grain boundary diffusion treatment, the remanent magnetism B r Increase by 0.30 kGs, and the coercive force H of the magnet cj Also increased from 3.61kOe to 6.27kOe, magnetic energy product (BH) m Increase 5.21MGOe. Grain boundary diffusion La 60 Al 30 Cu 10At the same time, the remanence, coercive force and magnetic energy product of the cerium-containing magnet are increased, achieving obvious beneficial effects.

[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A grain boundary diffusion source coating for improving the remanence of a (Ce, R)-Fe-B magnet, characterized in that: The grain boundary diffusion source coating is a powder, including the elements La, Al and Cu, expressed in atomic percentage as La 1-x-y Al x Cu y , where 25≤x≤0.35, 0.05≤y≤0.

15.

2. The grain boundary diffusion source coating according to claim 1, characterized in that: The average grain size SMD of the grain boundary diffusion source coating is 1 to 2 μm.

3. A method for improving the remanence of a (Ce, R)-Fe-B magnet, characterized in that: Using the grain boundary diffusion source coating according to claim 1 or 2 comprises the following steps: S1: Cut the original cerium-containing magnet that meets the mass percentage requirements into a cylindrical shape, clean the oil stains on the surface of the magnet, and polish with sandpaper to remove the oxide layer on the surface of the magnet; S2: According to the alloy mass percentage chemical formula La 1-x-y Al x Cu y Configure the raw materials, where 0.25≤x≤0.35, 0.05≤y≤0.15; S3: Preparation of La by smelting 1-x-y Al x Cu y Diffusion source alloy; S4: La 1-x-y Al x Cu y The diffusion source alloy is roughly crushed to obtain La 1-x-y Al x Cu y Diffusion source alloy coarse powder; S5: La 1-x-y Al x Cu y Diffusion source alloy coarse powder is hydrogen-crushed to obtain La 1-x-y Al x Cu y Diffusion source alloy hydrogen powder breaking; S6: La 1-x-y Al x Cu y The diffusion source alloy is crushed and powdered under the protection of anhydrous ethanol to obtain La 1-x- y Al x Cu y Diffusion source alloy powder slurry; S7: La 1-x-y Al x Cu y The diffusion source alloy powder slurry is applied to the surface of the cylindrical magnet in step S1 to obtain an attached diffusion source magnet; S8: subjecting the attached diffusion source magnet to grain boundary diffusion treatment and then to tempering treatment to obtain (Ce, R, La)2Fe 14 Grain boundary diffusion of cerium-containing magnets in the B shell.

4. The method for improving the remanence of a (Ce, R)-Fe-B magnet according to claim 3, characterized in that: In step S3, the smelting is one of electric arc furnace smelting, induction smelting, rapid quenching or rapid solidification.

5. The method for improving the remanence of a (Ce, R)-Fe-B magnet according to claim 4, characterized in that: In step S5, the hydrogen crushing and powder making process is: La obtained in step S4 1-x-y Al x Cu y The diffusion source alloy coarse powder is subjected to hydrogen cracking treatment, and is crushed by hydrogen absorption at room temperature and 0.1 MPa pressure to obtain hydrogen-crushed powder of 20 to 150 μm, without dehydrogenation treatment.

6. The method for improving the remanence of a (Ce, R)-Fe-B magnet according to claim 5, characterized in that: In step S6, the La 1-x-y Al x Cu y In the diffusion source alloy powder slurry, anhydrous ethanol and La 1-x-y Al x Cu y The mass ratio of the diffusion source alloy powder is 1:

1.

7. The method for improving the remanence of a (Ce, R)-Fe-B magnet according to claim 6, characterized in that: In step S7, the weight increase of the magnet with attached diffusion source is 0.4-0.6% of the weight of the original magnet.

8. The method for improving the remanence of a (Ce, R)-Fe-B magnet according to claim 7, characterized in that: In step S8, the grain boundary diffusion treatment temperature is 850-950° C., and the grain boundary diffusion treatment time is 3-24 hours.

9. The method for improving the remanence of a (Ce, R)-Fe-B magnet according to claim 8, characterized in that: In step S8, the tempering treatment temperature is 400° C. to 700° C., and the tempering treatment time is 2 to 5 hours.

10. A (Ce, R)-Fe-B magnet, characterized in that: The outer layer of the main phase grain of the (Ce, R)-Fe-B magnet includes (Ce, R, La)2Fe 14 B shell.